(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In old India, however man centric framework was profoundly common - all male mastery - ladies delighted in a place of regard and veneration. A few engravings make references to the status of ladies in that they appreciated the opportunity to make liberal blessings to religious foundations like sanctuaries, dharmasalas not simply for the welfare of leaders of the families however for their folks too. Ladies held vital position in old Indian culture. There are confirmations to recommend that lady control annihilated kingdoms and strong rulers. Elango Adigal’s Sillapathigaram made reference to that Madurai, the capital of Pandyas was scorched, when Pandyan ruler Nedunchezhiyan executed a lady’s significant other by oversight. Veda Vyasa’s Mahabharata recounts the account of the fall of Kauravas on the grounds that they mortified Draupadi. Valmiki’s. Ramayana is additionally about the obliteration of Ravana when kidnapped and endeavored to wed Sita coercively. The plenty of Goddesses in antiquated period was made to ingrain regard for ladies. Ardhanareshwar (God is half-man and half-lady) was exceedingly venerated. Ladies were permitted to have different spouses. They could leave their spouses. In this paper